Effects of exercise and environmental complexity on deficits in trace and contextual fear conditioning produced by neonatal alcohol exposure in rats. Issue 5 (29th May 2012) - Schreiber, W.B.; St. Cyr, S.A.; Jablonski, S.A.; Hunt, P.S.; Klintsova, A.Y.; Stanton, M.E.
Abstract In rodents, voluntary exercise and environmental complexity increases hippocampal neurogenesis and reverses spatial learning and long‐term potentiation deficits in animals prenatally exposed to alcohol. The present experiment extended these findings to neonatal alcohol exposure and to delay, trace, and contextual fear conditioning. Rats were administered either 5.25 g/kg/day alcohol via gastric intubation or received sham‐intubations (SI) between Postnatal Day (PD) 4 and 9 followed by either free access to a running wheel on PD 30–41 and housing in a complex environment on PD 42–72 (wheel‐running plus environmental complexity; WREC) or conventional social housing (SHSH) from PD 30 to 72. Adult rats (PD 80 ± 5) received 5 trials/day of a 10‐s flashing‐light conditioned stimulus (CS) paired with .8 mA footshock either immediately (delay conditioning) or after a 10‐s trace interval (trace conditioning) for 2 days. Neonatal alcohol exposure impaired context and trace conditioning, but not short‐delay conditioning. The WREC intervention did not reverse these deficits, despite increasing context‐related freezing in ethanol‐exposed and SI animals. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 483–495, 2013